Can Distributed Ledger Technology Reduce Earnings Management? - Wang, Keman (2019)
Distributed ledger technology （DLT） is the most popular fintech currently, which can effectively improve data transparency and traceability and prevent information modification. Because DLT could provide permanent, incorruptible and irreversible records, we assume that its application can reduce the space of accrual-based earnings management, and the application of DLT will encourage real earnings management activities due to the substitution relationship between accrual-based earnings management and real earnings management. The way of DLT application can be divided into direct application to financial data and indirect application to financial data. This paper assumes that direct application to financial data will reduce the space of accrual-based earnings management more significantly than the other way. This paper uses a cross-section analysis to regress 295 firm-year data in 2013-2018 which covers periods before and after the application of DLT to explore the impact on the level of two kinds of earnings management and regresses 75 firm-year data after DLT application to explore the impact of the way using DLT. It proves that the financial-direct application of DLT to financial institutions can limit the space of accrual-based earnings management, and the application of DLT will encourage companies with high growth rates to conduct real earnings management.